1996
DOI: 10.1007/bf00120493
|View full text |Cite
|
Sign up to set email alerts
|

Modification of catecholamine-induced changes in heart function by food restriction in rats

Abstract: In view of the common practice of dieting for weight reduction, the influence of severe food restriction (about 25% of ad libitum intake) on adrenergic mechanisms was studied. Cardiac norepinephrine and epinephrine concentrations as well as plasma norepinephrine levels, were increased upon feeding a restricted diet to rats for 14 days in comparison with control rats that ingested about 30 g food/ day. Bradycardia as well as characteristic electrocardiographic abnormalities, including prolongation of the QRS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Furthermore, there was a marked reduction in cell contractility in response to stimuli of increasing intensity, suggesting that low protein intake reduce the functional reserve in cardiomyocytes and responsiveness to sympathetic stimulation. Similar results were described by McKnight et al [18], indicating that a 75% dietary restriction was able to induce pathological changes in response to β-adrenergic stimulation in a preparation of isolated papillary muscle. These findings indicate that the myocardial contractile incompetence presents a cellular basis, which goes beyond the morphological changes of the heart parenchyma and stroma induced by protein restriction.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there was a marked reduction in cell contractility in response to stimuli of increasing intensity, suggesting that low protein intake reduce the functional reserve in cardiomyocytes and responsiveness to sympathetic stimulation. Similar results were described by McKnight et al [18], indicating that a 75% dietary restriction was able to induce pathological changes in response to β-adrenergic stimulation in a preparation of isolated papillary muscle. These findings indicate that the myocardial contractile incompetence presents a cellular basis, which goes beyond the morphological changes of the heart parenchyma and stroma induced by protein restriction.…”
Section: Discussionsupporting
confidence: 90%
“…Such a depression of the cardiovascular function is consistent with findings in which rats were fed 10 g of food per day for 6 weeks (Nutter et al 1979). More recently, similar results were obtained by McKnight et al (1996) andHilderman et al (1996) in food-deprived rats. The decrease in ABP and HR recorded during the first two cycles of deprivation could be partially due to the increase in noradrenergic activity of A1 and A2 cell groups, known to play a vasodepressor role.…”
Section: Cardiovascular Responsessupporting
confidence: 91%
“…Although FR apparently provides some beneficial effects, our previous publications (Cicogna et al 2000;Fioretto et al 2002;Gut et al 2003;Okoshi et al 2001Okoshi et al , 2002 and those by other investigators (Haddad et al 1993;Hilderman et al 1996;McKnight et al 1996;Katzeff et al 1997) have shown that dietary restriction impairs cardiac performance. The mechanisms behind these changes in myocardial function with FR remain unknown.…”
Section: Introductionmentioning
confidence: 83%